Enterprise ontology based knowledge map for improving hospital services - Musa, Mahdi Alhaji (2013)
The global healthcare spending has constantly increased in the last decades, and there is data showing inefficiency in resource consumption that is not reflected in healthcare improvement. The need to introduce new ways to do the same at a lower cost is rational. To address this, we propose a method based on Enterprise Ontology and knowledge map to find non value-added transactions that must be redesigned to improve the healthcare management. This methodology was chosen as a basis for our solution because it provides a better understanding of the dynamics of an organization, and allows a good alignment between the enterprise design and operation. Demonstrations were accomplished in University Teknologi Malaysia Healthcare Center, making it possible to find transactions that can be refined or improved. Results prove that the method yields an adequate and clear process view and is reliable when it comes to improving healthcare operational processes.